Clients acquisition and business relationship development of medical services evidence from: Mount Elizabeth hospitals Singapore, Dhaka office - Ahmed, Tanvir (BRAC University, 2024)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2023.